THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE AND CONGENITAL HYPOTHYROIDISM SCREENING IN NEWBORNS - Syarini Novita; Dewi Fajar Wati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Infants with Congenital Hypothyroidism who are not diagnosed and treated early are at risk of intellectual disability and growth impairment. Congenital Hypothyroidism Screening coverage for newborns at the Bukoposo Community Health Center in Mesuji, Lampung, during December 2025 to January 2026, reached only 25.9%. This study aimed to determine the extent to which maternal knowledge influences the uptake of Congenital Hypothyroidism Screening for newborns in this working area. A quantitative analytical survey with a cross-sectional design was employed. The study sample consisted of 99 mothers with infants aged 15 days to one month, selected using purposive sampling. Data were collected via questionnaires and analyzed using the Chi-square test. The results showed that among mothers with low knowledge, the majority (90%) did not have their infants screened, while only 10% did (p-value = 0.000; OR = 11.65). The study concludes that there is a very strong and significant relationship between the level of maternal knowledge and Congenital Hypothyroidism Screening uptake. Mothers with poor knowledge were far less likely to have their infants screened. These findings indicate a need for more extensive efforts to improve knowledge and provide education regarding newborn Congenital Hypothyroidism Screening to mothers in this area.